Differentiation of combined nevi and melanomas: Case‐control study with comparative analysis of dermoscopic features - Schweizer, Anissa; Müller-Christmann, Christine; Bertlich, Ines; Toberer, Ferdinand; Enk, Alexander; Kilian, Samuel; Hänßle, Holger (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Background and objectives - Combined nevi (CN) show two or more components of major nevus subtypes and simulate melanomas. We investigated a panel of dermoscopic features and three dermoscopic algorithms for differentiating CN from melanomas.